Removal of Heavy Metals from Wastewater Using Multiwalled Carbon Nanotubes - Suliman, Malaz (2017)
A Master of Science thesis in Chemical Engineering by Malaz Suliman entitled, "Removal of Heavy Metals from Wastewater Using Multiwalled Carbon Nanotubes," submitted in April 2017. Thesis advisor is Dr. Taleb Ibrahim. Soft and hard copy available.